Chile's National Advisory Committee on Immunization (CAVEI): Evidence-based recommendations for public policy decision-making on vaccines and immunization. Issue 32 (26th July 2019) - Dabanch, Jeannette; González, Cecilia; Cerda, Jaime; Acevedo, Johanna; Calvo, Mario; Díaz, Eduardo; Endeiza, María; Inostroza, Jaime; Rodríguez, Jaime; Saldaña, Adiela; Santillana, Solange; El Omeiri, Nathalie; et al.
Abstract: A National Immunization Technical Advisory Group (NITAG) provides independent, evidence–based recommendations to the Ministry of Health for immunization programmes and policy formulation. In this article, we describe the structure, functioning and work processes of Chile's NITAG (CAVEI) and assess its functionality, quality of work processes and outputs, and integration of the committee into the Ministry of Health policy process using the Assessment tool for National Immunization Technical Advisory Groups . Among its strengths, CAVEI's administrative and work plasticity allows it to respond in a timely manner to the Ministry of Health's requests and proactively raise subjects for review. Representation of multiple areas of expertise within the committee makes CAVEI a robust and balanced entity for the development of evidence–based comprehensive recommendations. High ranking profile of the Secretariat structure furthers CAVEI's competences in policymaking and serves as a bridge between the committee and international initiatives in the field of immunizations.